An efficient click-multicomponent strategy for the diversity oriented synthesis of 15–18 membered macrocyclic peptidomimetic fluorophores. Issue 19 (6th May 2015) - Jithin Raj, P.; Bahulayan, D.
Graphical abstract: Abstract: A general methodology for the three step synthesis of macrocyclic peptidomimetic fluorophores with a range of ring size from 15 to 18 is described. The alternate Mannich type reaction between the halogen functionalized long chain alkyl nitriles with aldehydes and ketones in which one of them decorated with an alkyne functionality leads to the key precursor for the intramolecular copper catalyzed [3+2] azide-alkyne cycloaddition to make the macrocycles obeying Lipinski's rule of five.